KAJIAN TEORITIS PEMISAHAN H2S DALAM BIOGAS SECARA ABSORBSI REAKTIF KE DALAM LARUTAN Fe-EDTA MENGGUNAKAN PACKED COLUMN - Ali Altway (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2009)
The presence of H2S in biogas gives dangerous effect on environment; Therefore, H2S must be eliminated from the biogas. The purpose of this research is to analyze theoretically the elimination process by reactive absorption of H2S in biogas into aqueous Fe-EDTA solution in packed column. This research was carried out by developing mathematical model of the process. The interfacial mass transfer phenomena were described by film model equations solved using van Krevelen approximation. Steady state, isothermal condition, and plug-like pattern of gas-liquid flow in packed column were assumed in this study. The model consists of differential mass balance of H2S in gas phase and Fe-EDTA in liquid phase arising system of non-linear first order differential equations solved numerically by Fourth order Runge-Kutta method under Mathlab facility. The system studied consists of a column 10 cm in diameter filled with 1cm raschig rings to the height of 100 cm. The gas flow rate was held constant at GV = 100 mL/s, liquid flow rate L’ was varied 20, 30, and 40 mL/s, pressure P was varied from 1 to 2.5 atm, the concentration of Fe-EDTA in inlet absorbent was varied from 0.02 to 0.06 kmol/m3. The experimental work was also carried out to validate the simulation prediction. The simulation results showed that the percentage of absorbed H2S can be enhanced by decreasing pressure, increasing temperature, liquid flow rate, and Fe-EDTA concentration The trend of pressure and temperature effect on % H2S recovery showed that the absorption process is controlled by the gas resistance. Using column with packing height of 1 meter, gas flow rate of 100 mL/s, using absorbent containing 0.06 kmol/m3 Fe-EDTA with flow rate of 20 mL/s, and at ambient pressure and temperature, the percentage recovery of H2S reached the value of above 99%. The simulation results agree very well with the experimental data within 3% error.